A darker shade of white: expat self-making in a Congolese rainforest enclave - Hendricks, T (Cambridge University Press, 2017)
This article offers a new perspective on contemporary ‘whiteness’ in Africa by looking at the ambiguous ways in which it affects everyday life in and around the labour compounds of a multinational timber firm in the Congolese rainforest. As a foreign investment enclave, the logging concession is home to a small isolated community of European expatriate men whose ‘white’ faces evoke a set of ambivalent memories of colonial exploitation in the area. Through a carefully contextualized understanding of how these contemporary expats are perceived in the labour compounds and how they construct their own racialized male selves, this article pushes the discussion on whiteness in Africa beyond the conventional analysis of (post-)settler identities and whites of African nationalities. It argues that, as a permanent fixture in the present neoliberal moment but also as an uncanny repetition of a colonial past, the European loggers construct and embody very specific ‘expat’ masculinities, whose internalized dynamics of self-exoticization make them ‘African’ in their own right. Mobilizing the problematic trope of ‘darkness’, both in expat self-making practices and in popular narratives about their presence, this article illustrates how whiteness in Africa comes in many shades.